Strengthening hepatitis B and C surveillance in Europe: results from the two global hepatitis policy surveys (2013 and 2014). Issue 1 (December 2016) - Lazarus, Jeffrey; Mozalevskis, Antons; Safreed-Harmon, Kelly; Eramova, Irina
Abstract Background Hepatitis B and C are major public health threats in the World Health Organization (WHO) European Region. Viral hepatitis surveillance shortcomings have resulted in many WHO Member States having insufficient data available to guide decision-making. This study describes surveillance in the region based on a quantitative sub-analysis of findings from the 2013 WHO viral hepatitis policy report and a qualitative analysis of civil society survey responses associated with these findings. Methods Descriptive statistics were created from information that national government focal points for viral hepatitis in 44 countries had previously reported in response to the WHO survey. Bivariate analysis was performed to compare data from within and outside of the European Union/European Economic Area (EU/EEA). Survey responses from civil society organizations in the countries of the WHO European Region were collated, and a descriptive analysis of the comments on surveillance-related questions was performed to identify key themes. Results The response rate for the survey of governments was 83 % among both EU/EEA countries (25/30) and non-EU/EEA countries (19/23). More than 90 % of governments reported having national surveillance systems for the acute forms of hepatitis B and hepatitis C, but less than two-thirds reported surveillance for the chronic forms of both diseases. High proportions of governments reported having central registries for the reporting of deaths (96 %) and liver cancer cases (80 %), while less than half reported regularly conducting viral hepatitis sero-surveys. All responding Member States reported having adequate laboratory capacity nationally to support hepatitis outbreak investigations and other surveillance activities. Target populations for sero-surveys most commonly included people who inject drugs (27 %), the general population (25 %), men who have sex with men (20 %) and pregnant women (20 %). Few statistically significant differences were found between EU/EEA and non-EU/EEA countries. Conclusions Study findings indicated a capacity for robust viral hepatitis surveillance across the WHO European Region, with most countries having important surveillance components in place, but notable weaknesses were also identified. There is an urgent need for countries throughout the region to strengthen their surveillance programs in order to maximize the population-level impact of advances in HBV and HCV prevention and treatment.